2011
DOI: 10.1016/j.juro.2010.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity, Treatment and Mortality: A Population Based Cohort Study of Prostate Cancer in PCBaSe Sweden

Abstract: Comorbidity affects treatment choices, and is associated with all cause, competing cause and conditional prostate cancer specific mortality. An increased conditional prostate cancer specific mortality in men with severe comorbidity may reflect less aggressive treatment, impaired tumor defense, lifestyle factors and poor general health behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 134 publications
9
95
0
Order By: Relevance
“…2 Our 10-year other-cause mortality estimates by Charlson score are similar to other mixed-treatment samples of men with prostate cancer obtained from administrative data or chart abstraction, 3,4 and may appear high due to the inclusion of only men aged 66 years. To ensure that our findings were robust across all ages, we repeated our comparative effectiveness models in age subgroups and found that men with Charlson scores of 3 do not benefit from aggressive treatment, regardless of their age at the time of diagnosis.…”
Section: Reply To Charlson Score and Competing Mortalitysupporting
confidence: 64%
See 1 more Smart Citation
“…2 Our 10-year other-cause mortality estimates by Charlson score are similar to other mixed-treatment samples of men with prostate cancer obtained from administrative data or chart abstraction, 3,4 and may appear high due to the inclusion of only men aged 66 years. To ensure that our findings were robust across all ages, we repeated our comparative effectiveness models in age subgroups and found that men with Charlson scores of 3 do not benefit from aggressive treatment, regardless of their age at the time of diagnosis.…”
Section: Reply To Charlson Score and Competing Mortalitysupporting
confidence: 64%
“…2 The subsequent suspension of power morcellator sales from Johnson & Johnson has increased concerns regarding the use of minimally invasive techniques for myomectomy and hysterectomy in cases of large uteri, thus potentially limiting the diffusion of minimally invasive procedures. 3 Two interesting points of the investigation by George et al 1 deserve to be addressed. The first is in regard to the cost-effectiveness and risk-to-benefit ratio between intraperitoneal morcellation of undiagnosed leiomyosarcoma and the execution of unnecessary open abdominal procedures in patients with leiomyomas.…”
Section: In-bag Morcellation For Presumed Myoma Retrieval At Laparoscopymentioning
confidence: 99%
“…In May 2016, NPCR was linked to the Prescribed Drug Registry, the Patient Registry, the Cause of Death Register, the Longitudinal database on socioeconomic factors (acronym in Swedish LISA) and the Register of Total Population and Population changes to generate Prostate Cancer data Base Sweden (PCBaSe) RAPID. As previously described, Charlson Comorbidity Index (CCI) was calculated based on discharge diagnoses in the Patient Registry by use of 17 groups of diseases with each diagnosis assigned a specific weight (1, 2, 3 and 6) and the sum of these weights resulted in three levels of CCI: 0 for no comorbidity, 1–2 for mild to moderate, and 3+ for severe comorbidity 12, 13…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, Charlson Comorbidity Index (CCI) was calculated based on discharge diagnoses in the Patient Registry by use of 17 groups of diseases with each diagnosis assigned a specific weight (1, 2, 3 and 6) and the sum of these weights resulted in three levels of CCI: 0 for no comorbidity, 1-2 for mild to moderate, and 31 for severe comorbidity. 12,13 Information on educational level, annual disposable income, and marital status was retrieved from the LISA database. Men were categorized according to the highest attained level of education, into low (<10 years mandatory school), intermediate (10-12 years high school), and high (university or college).…”
Section: Study Populationmentioning
confidence: 99%